The role of rock fragments in crack and soil structure development: a laboratory experiment with a Vertisol. (26th May 2015) - Gargiulo, L.; Mele, G.; Terribile, F.
Summary A large number of factors that influence soil surface cracking behaviour in swell‐shrink soils have been studied, but there are few studies on the influence of rock fragments on crack development. Effects of rock fragments have been investigated with reference to the soil pore system but they have mainly been studied indirectly through measurements of water flow and/or bulk density changes. A laboratory experiment was carried out with repacked soil samples that were prepared by adding rock fragments of three different sizes (2–4, 4–8 and 12–16 mm) to a Vertisol at two different rates (10 and 25% by volume). Soil image analysis procedures were applied in order to describe quantitatively the network of surface cracks and the pore system to a depth of 8 cm below the surface, which developed after wetting‐drying cycles. Mean values and standard deviations of surface crack or pore widths decreased with the increase in rock fragment content and the decrease in rock fragment size, while the density of the 'skeleton' of the crack and pore networks increased. Rock fragments also induced vertical homogenization of the soil structure. The number of rock fragments was a key factor in determining some crack network characteristics, inducing inverse variations in mean width and skeleton density of the crack or pore network. Overall results suggested that rock fragments acted as triggering points for crack and pore development in Vertisols. The findings of this work provide a contribution to the understanding of the mechanisms of crack network and soil structure development that are induced by stones in swell‐shrink soils.